EVALUATION OF PHARMACEUTICAL CARE STANDARD IMPLEMENTATION BY PHARMACIST IN BANTUL RESIDENCE’S PHARMACY - Prabasiwi Nur Fauziyah; Satibi Satibi (Faculty of Pharmacy, Universitas Gadjah Mada)
Indonesia Health Ministrial Decree No. 1027/2004 has been published as a standard of quality assurance in pharmaceutical care provided by pharmacist. As the time goes by, the newest regulation has been provided by government through PP No. 51/2009 to legitimate pharmacists in their responsibility as role player in pharmaceutical care. The implementation of this policy, however, is still unknown yet and needs to be further evaluated. The study aimed to evaluate the pharmaceutical care standard implementation by pharmacist according to this regulation. This research involved pharmacists in 32 pharmacies in Bantul as respondents. These pharmacies was selected by proportional random from the total of 108 pharmacies in 16 district of Bantul Residence. The data was collected through questionnaire and analized descriptively according to indicators; administration; drug and prescription service; communication, information, and education, inventory control management, human resources, supporting facilities, and evaluation of service quality. The result was categorized as good if total score persentation 81-100%, adequate if total score persentation 61-80%, and less if total score persentation ≤60%. The study result showed that generally the pharmaceutical care standard has not been well implemented in Bantul Residence. There were 18 pharmacies (56.25%) in the good category, 13 pharmacies (40.63%) in the adequate category, and 1 pharmacy (3.13%) in the less category. The indicators that have been well implemented were supporting facilities indicator (88.95%), human resources indicator (887.67%), inventory control management (82.29%). Other indicators including Communiation, Information, and Education (75.63%), administration (68.23%), and drug and prescription service (64.95%) were in the less category.Keywords: Pharmaceutical Care Standard, Kepmenkes No. 1027/2004, PP No. 51/2009, Bantul Residence